STRUKTUR KEPEMILIKAN, UKURAN PERUSAHAAN DAN PRAKTEK CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA - Reni Yendrawati; Wahyu Agung Setyo Nugroho (University of Merdeka Malang, 2012)
Many companies conducted earnings management in order to attract potential investors. The extent to whichthose companies undertook profit management was influenced by many factors, such as: ownership structure,company size and corporate governance practices. The objective of this study was to determine the effect ofownership structure, company size and corporate governance practices toward earnings management. Ownershipstructure was the proxy of management ownership, and firm size was the proxy of the log of total assets.In addition, corporate governance was measured by the composition of the board of commissioners and industryspecialization of audit firm. The companies used in this study were 16 LQ 45 firms from the year 2008 to2010. The method of analysis used in this study was multiple linear regressions. The results showed that thecomposition of commissioner board had a significant negative effect on earnings management while the otherthree variables, namely the ownership structure, firm size, and KAP industry specialization did not affectsignificantly toward earning management.